(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The purpose of this study is to describe and analyze the influence of idealism, inspirational motivation, intellectual stimulation, and individual awareness of the principal’s leadership on improving the quality of education at SDN Beji 01. This research is descriptive qualitative; the subjects were the principal, teachers, and educational staff. Data collection techniques included interviews, documentation, and observation. Qualitative analysis was used, encompassing data collection, data reduction, data display, and drawing conclusions. The results of the study indicate that: (1) The influence of the principal’s leadership idealism includes: the ability to organize and influence school members to implement the school’s vision and mission; providing an example; creating educational programs based on educational quality standards; creating a conducive and comfortable work environment, and motivating all school members to participate in improving the quality of education.(2) The principal’s leadership inspirational motivation includes: providing advice, direction, guidance, and inspirational encouragement and motivation to school members; providing examples of time discipline, working hard, and adhering to shared commitments; and providing support to teachers and staff to develop their careers. (3) The principal’s leadership intellectual stimulus includes: creating a collaborative culture and teamwork; cultivating problem solving through a system of discussion and deliberation; encouraging teachers and students to think critically, creatively, and innovatively; creating a learning atmosphere that is in line with development sin science and technology; accepting criticism and ideas; and creating a culture of transparency. (4) The principal’s leadership individual awareness includes: providing attention and concern for teachers and staff; holding regular meetings; involving teachers and staff in decision-making; providing time for personal consultations; giving awards; development of teacher professionalism through principal supervision. The impact of transformational leadership is the influence and encouragement of school residents to make better changes, teachers have adequate competence and the school achieves various kinds of achievements, both academic and non-academic.